Psychological risks experienced by interpreters in the domestic violence cases: a systematic review - Guo, Ning; Muurlink, Olav; Doyle, Shane (Frontiers in Sociology, 2023)
Interpreters occupy a complex position in police interviews involving domestic violence cases—neutral but necessary parties to traumatic content. The following systematic review explores the relatively sparse scholarly literature on interpreters' psychological responses to being a party to domestic violence interviews in a policing context. This article aims to explore themes of relevant studies targeting interpreters' mental health in such cases, with nine articles emerging from a comprehensive search of eight databases supplemented with a Google Scholar search. Various themes involving interpreters emerged from the ensuing analysis, including intrinsic difficulties, misguided expectations, role requirements, psychological impacts, posttraumatic growth, coping strategies, and recommendations for future research and practice, with findings holding implications for interpreting in other traumatic domains.